2008
DOI: 10.1001/archpediatrics.2007.45
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of the Effects of Reducing Television Viewing and Computer Use on Body Mass Index in Young Children

Abstract: To assess the effects of reducing television viewing and computer use on children's body mass index (BMI) as a risk factor for the development of overweight in young children.Design: Randomized controlled clinical trial.Setting: University children's hospital.Participants: Seventy children aged 4 to 7 years whose BMI was at or above the 75th BMI percentile for age and sex.Interventions: Children were randomized to an intervention to reduce their television viewing and computer use by 50% vs a monitoring contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
462
2
13

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(491 citation statements)
references
References 48 publications
14
462
2
13
Order By: Relevance
“…The interesting finding of the differential impact of interventions as a function of socio economic status (SES), seen in this study, has not been examined in most studies and mixed findings have been reported in few recent studies. 18,25 In the Kiel Obesity Prevention Study, 25 the effect of an education program involving nutrition education and increased activity at school on prevalence of overweight at 4-year follow-up was significant in children from families with high SES. In contrast, Epstein et al 18 found that with an intervention targeting only television viewing and computer use over a 2-year period, change in BMI z-score was significant only in children from families of low SES.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interesting finding of the differential impact of interventions as a function of socio economic status (SES), seen in this study, has not been examined in most studies and mixed findings have been reported in few recent studies. 18,25 In the Kiel Obesity Prevention Study, 25 the effect of an education program involving nutrition education and increased activity at school on prevalence of overweight at 4-year follow-up was significant in children from families with high SES. In contrast, Epstein et al 18 found that with an intervention targeting only television viewing and computer use over a 2-year period, change in BMI z-score was significant only in children from families of low SES.…”
Section: Discussionmentioning
confidence: 99%
“…18,25 In the Kiel Obesity Prevention Study, 25 the effect of an education program involving nutrition education and increased activity at school on prevalence of overweight at 4-year follow-up was significant in children from families with high SES. In contrast, Epstein et al 18 found that with an intervention targeting only television viewing and computer use over a 2-year period, change in BMI z-score was significant only in children from families of low SES. Similarly, Foster et al 26 showed that a multicomponent school-based intervention for 2 years involving older children (mean age 11 years) from low SES, resulted in marked reduction in the prevalence of overweight; odds ratios and 95% confidence interval were 0.65 (0.54-0.79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, 39.5% of non-Hispanic black adolescents are considered overweight or obese as defined by body mass index greater than or equal to sex-and age-specific 85th percentile from the 2000 CDC Growth Charts (Ogden, et al, 2010). Previous studies have demonstrated significant positive associations between sedentary behaviors, including screen time, and adolescent weight status (Eisenmann, Bartee, Smith, Welk, & Fu, 2008;Epstein et al, 2008;Mitchell et al, 2009;Robinson, 1999). These associations are especially troubling among African American youth, given that 55.5% of African American adolescents report watching !3 hr of television per day as compared with the national average of 32.8% (Eaton et al, 2010).…”
mentioning
confidence: 99%
“…Often persisting into adulthood, childhood obesity increases the risk of suffering from a range of diseases, including diabetes mellitus and CVD, which can lead to poor quality of life and a shortened lifespan (3)(4)(5) . Overweight among children is related to many factors at the individual, family and environmental levels.Cross-sectional and longitudinal studies have shown a positive association between time spent watching television (TV) and an increase in the prevalence of childhood overweight and obesity (6)(7)(8)(9) ; whereas the results of published studies indicate a positive relationship between TV viewing and overweight (10)(11)(12) , mechanisms driving this are not clear. Two primary mechanisms by which TV viewing contributes to weight gain in children have been suggested: reduced physical activity or increased energy intake or a combination of both.…”
mentioning
confidence: 99%